Funeral Poverty: An Exploratory Study for Micro-Takaful - Azrul Azlan Iskandar Mirza; Khairil Faizal Khairi; Syadiyah Abdul Shukor; Nurul Aini Muhamed; Ahmad Fadly Nurullah Rasedee; Muhammad Suhaimi; Nuur Halimatus Saadiah Masrukhin; Aimi Fadzirul Kamarubahrin (Tazkia Islamic Finance and Business Review, 2020)
The funeral expense is becoming expensive. It will lead into funeral poverty whereby the next of kin of the deceased face a difficulty to pay funeral expenses. The funeral poverty already affected developed countries such as Indonesia and African countries. For Malaysia, few schemes have been established by society to cover the poor from having difficulties for funeral expenses. The underlying reason behind the practice is a strong culture and belief. Nevertheless, these organizations have a different approach in managing this scheme but create chaos in the society from the perspective of payment and coverage. This paper will review literature, segmenting the practices and suggest the probable solution for funeral expenses scheme with the kind of exploring a segment in Takaful and micro-Takaful.